2022
DOI: 10.1002/rhc3.12248
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and perceptions of drought: A case study of two cities of Alabama

Abstract: Drought poses serious risks to society. There is, however, a lack of timely public awareness and sufficient public risk perceptions of this hazard due to its gradual onset. Timely and adequate public response is conducive to effective mitigation. It is imperative to understand how the public responds to drought. Using data from multiple sources, situated in two cities (Mobile and Huntsville) of Alabama, our study represents a comprehensive effort to understand public awareness and perceptions of drought. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…There are several independent variables that can influence the perception of drought, such as socio-economic status, age, education level, Income, household size, cultural beliefs, personal experience with drought, the frequency and severity of droughts in the past, the level of media coverage, and the overall level of environmental awareness in given region can also play role in shaping perception of drought [40][41][42][43][44][45]. However, it is difficult to identify a single independent variable that consistently affects how individuals perceive and respond to drought conditions.…”
Section: Drought Occurrence and Adaptationmentioning
confidence: 99%
“…There are several independent variables that can influence the perception of drought, such as socio-economic status, age, education level, Income, household size, cultural beliefs, personal experience with drought, the frequency and severity of droughts in the past, the level of media coverage, and the overall level of environmental awareness in given region can also play role in shaping perception of drought [40][41][42][43][44][45]. However, it is difficult to identify a single independent variable that consistently affects how individuals perceive and respond to drought conditions.…”
Section: Drought Occurrence and Adaptationmentioning
confidence: 99%
“…In particular for drought, awareness is typically low and delayed among the public, due to its slow onset, spatiotemporal variation and delayed impact on harvests (Shao et al, 2022;Wens et al, 2019). Until now, much effort has been made to understand the physical characteristics and the mechanism of drought (Hoerling et al, 2013).…”
Section: Risk Perceptionmentioning
confidence: 99%
“…After a record breaking drought in Texas in 2011, residents were significantly more concerned with water availability and water conservation [8]. A recent study on two cities in Alabama found that public awareness of drought is significantly dependent on geographic, physical, and social contexts [9]. They used Google Trends data in addition to survey data and suggested that future studies consider Twitter data to gain a more complete understanding of social responses to drought hazards.…”
Section: Introductionmentioning
confidence: 99%